Underpricing Care: A Case Study of Australia's National Disability Insurance Scheme. (1st December 2018) - Cortis, Natasha; Macdonald, Fiona; Davidson, Bob; Bentham, Eleanor
Abstract : Using a case study of Australia's National Disability Insurance Scheme, this article examines the role of prices in individualised funding schemes. It argues that prices were set too low to cover the full costs of disability support, placing pressure on relationship-building and other tasks required for high-quality care. We argue that the use of prices as mechanisms for cost containment in individualised funding schemes is predicated on the undervaluation of care. Our analysis can inform discussion among scholars, activists, policymakers and others about the design and impact of individualised funding, and the challenge of fully valuing care under market-based approaches.